Penerapan Metode Pembelajaran Aktif dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Adireza, Rifal; Julia, Julia; Nugraha, Rana Gustian (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This classroom action research is based on the use of a learning model that cannot train students in critical thinking, causing low student thinking. The purpose of this research is to improve students' critical thinking skills using an active learning method, namely PBL (Problem Based Learning). This class action research is carried out in accordance with the PTK stages, namely the initial condition (pre-action), action (action), and result (post-action). The material used in this study is the material of Changing the Form of Objects. The research was carried out in two cycles or two meetings. The stages of each cycle are planning, implementation, observation, and reflection. The assessment of critical thinking skills uses test questions in the form of PG questions as many as 10 items and descriptions as many as 3 items. The object of the research was 15 students in grade III of SDN Sukasirna I. The data collection techniques used in this study are observation and written tests. The data analysis techniques used are using qualitative data analysis and quantitative data analysis. The results of the research showed a significant increase by using the active learning method in improving students' critical thinking from cycle I and cycle II